1999
DOI: 10.1530/eje.0.1410358
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of serum calcidiol in an African population compared to a North European population

Abstract: Objective: To compare vitamin D status in an African population living at 10 ЊN with a Norwegian population living at 60 ЊN. Design: Serum samples from 30 healthy young Ethiopians and 31 full term pregnant women from Addis Ababa were collected in September, and from 24 healthy Norwegians in March and 23 pregnant women from Oslo in February to June. Methods: Serum (s) levels of calcidiol and intact parathyroid hormone (iPTH) were measured. Results:The median values for s-calcidiol were significantly lower in Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 15 publications
4
29
0
1
Order By: Relevance
“…In addition, darkly pigmented skin reduces the amount of UV light available in the skin for production of vitamin D. A comparative study carried out in Ethiopia has demonstrated that both ordinary Ethiopians and full term pregnant Ethiopian women living in Addis Ababa have a significantly decreased vitamin D status compared with pregnant Norwegian women living in Oslo [23].…”
Section: An Overviewmentioning
confidence: 99%
“…In addition, darkly pigmented skin reduces the amount of UV light available in the skin for production of vitamin D. A comparative study carried out in Ethiopia has demonstrated that both ordinary Ethiopians and full term pregnant Ethiopian women living in Addis Ababa have a significantly decreased vitamin D status compared with pregnant Norwegian women living in Oslo [23].…”
Section: An Overviewmentioning
confidence: 99%
“…The vitamin D status of almost all populations in sub-Saharan Africa is unknown but, from the incomplete data available, is lower in South Africa compared with the tropical African countries. 29 However, even near the equator, there can be a high rate of vitamin D deficiency, as demonstrated in adults in Ethiopia (10°N) 30 and Guinea-Bissau (12°N). 31 Nutritional rickets remains prevalent in some tropical countries despite good sunshine exposure, although this may be as a result of a low calcium intake rather than a deficiency in vitamin D. 32 From many studies covering a variety of approaches, it can be concluded that UVR and/or vitamin D have the potential to protect against some inflammatory diseases and autoimmune diseases, such as multiple sclerosis, while decreasing the immune surveillance against skin tumours and infectious diseases.…”
Section: Immunosuppression and Effects On Diseasesmentioning
confidence: 99%
“…[6][7][8] Buna keza, son yıllardaki yaşam koşullarındaki değişiklikler, kapalı alan aktivitelerinin artması ve cilt kanseri endişesiyle güneşten korunma, tüm dünyada olduğu gibi ülkemizde de gebelikte vitamin D eksikliğinin yaygın görülmesine yol açmaktadır. [9][10][11] Yenidoğan geçici takipnesi (YGT), yaşamın ilk günlerinde görülen solunum sıkıntısının en yaygın sebebidir. 12,13 Etiyopatogenezindeki esas mekanizma, fetal akciğer sıvısının gecikmiş rezorpsiyonudur.…”
unclassified